Use of a wiki as an interactive teaching tool in pathology residency education: Experience with a genomics, research, and informatics in pathology course - Seung Park; Anil Parwani; Trevor MacPherson; Liron Pantanowitz (Elsevier, 2012)
Background: The need for informatics and genomics training in pathology is critical, yet limited resources for such training are available. In this study we sought to critically test the hypothesis that the incorporation of a wiki (a collaborative writing and publication tool with roots in "Web 2.0") in a combined informatics and genomics course could both (1) serve as an interactive, collaborative educational resource and reference and (2) actively engage trainees by requiring the creation and sharing of educational materials. Materials and Methods: A 2-week full-time course at our institution covering genomics, research, and pathology informatics (GRIP) was taught by 36 faculty to 18 second- and third-year pathology residents. The course content included didactic lectures and hands-on demonstrations of technology (e.g., whole-slide scanning, telepathology, and statistics software). Attendees were given pre- and posttests. Residents were trained to use wiki technology (MediaWiki) and requested to construct a wiki about the GRIP course by writing comprehensive online review articles on assigned lectures. To gauge effectiveness, pretest and posttest scores for our course were compared with scores from the previous 7 years from the predecessor course (limited to informatics) given at our institution that did not utilize wikis. Results: Residents constructed 59 peer-reviewed collaborative wiki articles. This group showed a 25% improvement (standard deviation 12%) in test scores, which was greater than the 16% delta recorded in the prior 7 years of our predecessor course (P = 0.006). Conclusions: Our use of wiki technology provided a wiki containing high-quality content that will form the basis of future pathology informatics and genomics courses and proved to be an effective teaching tool, as evidenced by the significant rise in our resident posttest scores. Data from this project provide support for the notion that active participation in content creation is an effective mechanism for mastery of content. Future residents taking this course will continue to build on this wiki, keeping content current, and thereby benefit from this collaborative teaching tool.